Digital transformation in the automotive supply chain: trends and cases - Krykavskyy, Yevhen; Stasiuk, Kateryna (Scientific Journal of Bielsko-Biala School of Finance and Law, 2022)
Logistics system efficiency has a major impact on the level of the country's economy, thus the area deserves special attention. The New Reality of the Next Decade (VUCA) characterizes the modern market by the following features: volatility, uncertainty, complexity and ambiguity. Besides, the trends already formed in such conditions are specifically exacerbated and emphasized. Two main ones among those for the global logistics area include digital and sustainable supply chain. The automotive industry has a leading role in the world economy, so it has a direct impact on its development. The article considers current state and up-to-date digital solutions targeted at the industry. These topics are going to be covered by the main directions of digital transformation overview, in-depth explanation of their importance for the success along with some practical examples presentation for the cases of automotive industry digital transformation